Ten sleep - Belardes, Nicholas (Erewhon Books, an imprint of Kensington Publishing Corp., 2025)
When Greta Molina's old friend Tiller offered her the job, a ten-day cattle drive across the Wyoming prairie from the ranching town of Ten Sleep, it sounded like a well-paid break. Three hundred and twenty cows and calves, two guys her age she's known since college, and a few long days on an ATV will give her time to sort out the mess in her head. The canyon along the trail has a history, sure, but nature has a tendency toward violence. Greta can accept that, even if it makes her insides squirm. What Greta doesn't know is the legacy of murder and rot that runs deep into the rocks of this land. As each night passes on the prairie, the trio faces mounting supernatural dangers: a ghost train of the damned, wild animals walking alongside dead ones -- and evidence of a gigantic creature in the skies, one that's supposedly been extinct for eons. And Tiller may be hiding even darker secrets the further they go. Safety is only ten sleeps away, but Greta soon realizes that may be too long for all of them to survive.--